The Impact of Sweet Beverage Consumption and Socioeconomic Factors on Mental Health Disorder Symptoms in Indonesia - Vierra Citra Dewi Suchendar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to analyze the impact of sugary drink consumption and socioeconomic factors on mental health symptoms in Indonesia. Mental health is a crucial aspect of individual well-being, closely linked to a person's ability to manage stress, function productively, and contribute positively to themselves and their surroundings. This study highlights two main factors that can affect mental health: sugary drink consumption and socioeconomic factors. The methodology used in this research is a quantitative analysis using secondary data from IFLS 5, which includes indicators of mental health, consumption patterns, and the socioeconomic status of respondents. The results show that sugary drink consumption has a significant positive impact on the probability of depression symptoms. Meanwhile, socioeconomic variables such as education level, marital status, and wealth also influence the probability of depression symptoms.